1984
DOI: 10.1017/s0001566000007546
|View full text |Cite
|
Sign up to set email alerts
|

Situs Viscerum Specularis in Monozygotic Twins

Abstract: A case is reported of a 14-year old male MZ twin pair, with only one partner affected by situs viscerum inversus, whereby the condition is termed situs viscerum specularis. The high degree of mirror imaging is seen as an abnormal variation of the biological time of the cleavage giving rise to MZ twinning. Electrocardiographic findings are presented and the biological implications of the condition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
(5 reference statements)
0
15
0
1
Order By: Relevance
“…This has been reported in the chest, [24,25] in which mirror-image twins had chest tumors on the opposite sides, as well as in urologic situations [26,27] (in which mirror-image monozygotic twins simultaneously present with posterior urethral valves on opposite sides with respective hydronephrosis, necessitating reimplantation of the ureter into the bladder diverticulum for both twins). Situs inversus has also been reported in the heart [28].…”
Section: Discussionmentioning
confidence: 71%
“…This has been reported in the chest, [24,25] in which mirror-image twins had chest tumors on the opposite sides, as well as in urologic situations [26,27] (in which mirror-image monozygotic twins simultaneously present with posterior urethral valves on opposite sides with respective hydronephrosis, necessitating reimplantation of the ureter into the bladder diverticulum for both twins). Situs inversus has also been reported in the heart [28].…”
Section: Discussionmentioning
confidence: 71%
“…Situs inversus dextrocardia is situs inversus totalis because of the cardiac position as well as the atrial chambers and reversed abdominal viscera. [1,2,3,8,9,10] Cardiac situs is determined by the location of the atria. In both situs solitus and situs inversus, the ventricles may present in two positions.…”
Section: Discussionmentioning
confidence: 99%
“…It affects 0.001 % to 0.01 % people with a male to female ratio of 3:2 (5). Situs inversus is generally an autosomal recessive genetic condition, although it can be X-linked or found in identical "mirror" twins (6). Situs inversus totalis is accompanied with different diseases; Toros and friends showed that salivary gland choristoma of the middle ear in a child with situs inversus totalis (7).…”
Section: Discussionmentioning
confidence: 99%